The ZEW - Creditreform business survey in the business-related services sector : sampling frame, stratification, expansion and results - Ulrich Kaiser; Markus Kreuter; Hiltrud Niggemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
No other area of the German economy has developed so emphatically in the past ten years as has that business-related services. Regardless of its growing overall economic importance, official statistics fail to provide economic researchers and economic policy with current data on the business-related service sector. In such a situation where quantitative information about certain sectors is lacking, data obtained from business survey give important information on the state of the economy. The outcome of such surveys crucially depends on the expansion factors attached to the responses of individual firms. In this paper it is shown how a robust method of calculating expansions factors can be obtained using known auxiliary totals from the population. Robust in the sense means that the expanded data of the ZEW/Creditreform business survey are insensitive to changes in the sample design while the non-expanded data are not.
Keywords: C81; C42; 330; expansion factors; business-related services; Unternehmensdienstleistung; Konjunkturumfrage; Stichprobenverfahren; Deutschland